Evaporation with the formation of chains of liquid bridges. (5th January 2018) - Chen, C.; Joseph, P.; Geoffroy, S.; Prat, M.; Duru, P.
Abstract : The objective of the present work is to study the drying of a quasi-two-dimensional model porous medium, hereafter called the micromodel, initially filled with a pure liquid. The micromodel consists of cylinders measuring 50 [STIX]x03BCm in both height and diameter, radially arranged as a set of neighbouring spirals and sandwiched between two horizontal flat plates. As drying proceeds, air invades the pore space and elongated liquid films trapped by capillary forces form along the spirals. These films consist of 'chains' of liquid bridges connecting neighbouring cylinders. They provide hydraulic connectivity between the central bulk liquid cluster and the external rim of the cylinder pattern, where evaporation takes place during a first constant-evaporation-rate drying stage. The first goal of the present paper is to describe experimentally the phase distribution during drying, notably the evolution of liquid films, which controls the evaporation kinetics (e.g. the depinning of the films from the external rim signals the end of the constant-evaporation-rate period). Then, a viscocapillary model for the drying process is presented. It is based on numerical simulations of a liquid film capillary shape and viscous flow within a film. The model shows a reasonably good agreement with the experimental data. Thus, the present study is a step towards direct modelling of the effect of films on the drying of more complex porous media (e.g. packing of beads) and should be of interest for multiphase flow applications in porous media, involving transport within liquid films.